Leadership and power : identity processes in groups and organizations - Knippenberg, Daan van, 1966-; Hogg, Michael A., 1954- (London ; Thousand Oaks, Calif. : SAGE, 2003)
Leadership and associated power issues lie at the core of group life in a variety of contexts. Even the most informal of groups typically have some form of leadership in their organization, and the understanding of leadership and power from a psychological standpoint can inform a greater understanding of group dynamics both inside and outside of the workplace.
Identity, leadership, and power : preface and introduction / Daan van Knippenberg and Michael A. Hogg -- Leadership effectiveness : functional, constructivist and empirical perspectives / Martin M. Chemers -- Leader-member relations and social identity / Michael A. Hogg, Robin Martin, and Karen Weeden -- Leadership as the outcome of self-categorization processes / Michael J. Platow [and others] -- Identity, leadership categorization, and leadership schema / Robert Lord and Rosalie Hall -- Status characteristics and leadership / Cecilia L. Ridgeway -- Few women at the top : how role incongruity produces prejudice and the glass ceiling / Alice H. Eagly -- Justice, identity and leadership / Tom R. Tyler -- A relational perspective on leadership and cooperation : why it matters to care and be fair / David de Cremer -- Leadership, identity and influence : relational concerns in the use of influence tactics / Barbara van Knippenberg and Daan van Knippenberg -- Power and prejudice : a social-cognitive perspective on power and leadership / Stephanie A. Goodwin -- Power, social categorization, and social motives in negotiation : implications for management and organizational leadership / Carsten K.W. de Dreu & Gerben A. van Kleef -- Aberrations of power : leadership in totalist groups / Robert S. Baron, Kevin Crawley, and Diana Paulina -- The imperatives of identity : the role of identity in leader judgment and decision making / Roderick M. Kramer -- On the science of the art of leadership / Stephen Reicher and Nick Hopkins -- Identity, power, and strategic social categorizations : theorizing the language of leadership / Scott A. Reid and Sik Hung Ng.
Includes bibliographical references (pages 224-256) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Leadership; Power (Social sciences); Group identity; Intergroup relations; Organizational behavior; Leadership; Pouvoir (Sciences sociales); Identité collective; Relations intergroupes; Comportement organisationnel; group identity; POLITICAL SCIENCE -- Political Process -- Leadership; Organizational behavior; Intergroup relations; Group identity; Leadership; Power (Social sciences); Organisation; Identität; Sozialpsychologie; Führung; Macht; Leiderschap; Aufsatzsammlung